Flammability and serotiny as strategies: correlated evolution in pines - Schwilk, Dylan W.; Ackerly, David D. (Oikos, 2001)
Fire may act as a selective force on plants both through its direct effects by killing or wounding susceptible individuals and through its effect on the environment: the post-fire environment may select specific physiological traits or life histories. We used phylogenetic independent contrasts to test the hypothesis that fire has selected for correlated evolution among alternative suites of traits in pines: a survival/avoidance suite characterized by thick bark, height, and self-pruning of dead branches; and a fire-embracing strategy in which plants invest little into survival, exhibit traits which enhance flammability, and use fire as a means to cue seedling establishment to the post-fire environment through serotinous cones. We created a set of alternative 'supertree' phylogenies for the genus Pinus from published sources. Using these alternative phylogenies, published ecological data for 38 pine species, and newly collected morphological data, we demonstrate that much variation in trait evolution occurs along a fire-surviving/fire-embracing axis. Pines vary in their susceptibility to ignition since a tree that retains dead branches is more likely to carry a fire into the canopy than a tree that self-prunes. The evolution of increased flammability may have altered evolutionary trajectories prompting an evolutionary switch from a fire-surviving to a fire-embracing life history. Alternatively, the fire-embracing strategy may in fact select for increased flammability to ensure canopy ignition and the realization of serotinous seed-release.